PEMIJAHAN IKAN BETOK (Anabas Testudineus Bloch) YANG DIRANGSANG EKSTRAK HIPOFISA IKAN BETOK DENGAN RASIO BERAT IKAN DONOR DAN RESIPIEN BERBEDA - jaka prasetya; muslim .; mirna fitrani (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT The purpose of this research were to determine the best ratio of injection pituitary extract of climbing perch, latency time, amount of egg, percentage fertilized of egg, percentage hatching of egg and survival rate of climbing perch pro larvae. The research was conducted at Laboratorium Dasar Perikanan, Department of Aquaculture, Agriculture Faculty, Sriwijaya University since September until November 2014. The research used completely randomized design with 4 treatments and 3 replications. Those were P1 (1 donors : 1 recipient), P2 (2 donors: 1 recipient), P3 (3 donors : 1 recipient) and K(+) (®ovaprim 0.5 ml/kg). Based on to the honest significant different test showed that climbing perch pituitary extract injection of different ratio of weight fish had significantly different to latency time, amount of egg rate, percentage fertilized of egg but it’s not significantly different to percentage hatching of egg and survival rate. The best spawning latency time was P3 (9 hours 25 minutes), amount of egg was K(+) (10,123 grain), the highest percentage fertilized of eggs was P3 (98.25 %), the highest hatching percentage of eggs was P2 (93.90 %) and the highest survival rate pro larvae of climbing perch was P1 (87.71 %). Keywords: climbing perch, spawning, different weight ratio, donor, recipient